GPS tracking reveals rafting behaviour of Northern Gannets (Morus bassanus): implications for foraging ecology and conservation. Issue 1 (2nd January 2016) - Carter, Matt I. D.; Cox, Samantha L.; Scales, Kylie L.; Bicknell, Anthony W. J.; Nicholson, Matthew D.; Atkins, Kelly M.; Morgan, Greg; Morgan, Lisa; Grecian, W. James; Patrick, Samantha C.; Votier, Stephen C.
Abstract : Capsule Three quarters of tracked Northern Gannets ( Morus bassanus ) at Grassholm gathered in rafts around the colony, concentrated within a recently designated at-sea Special Protection Area (SPA), but rafting was not correlated with foraging effort. Aims To investigate the incidence, distribution and foraging implications of Northern Gannet rafting behaviour in waters adjacent to a large colony. Methods Using bird-borne global positioning system (GPS) loggers we reconstructed at-sea movement and used a speed filter to identify rafting behaviour within 10 km of the colony. We mapped the spatial distribution of rafting events from 160 breeding individuals over 5 years, and investigated the relationship between foraging effort (trip duration and total distance travelled) and the presence/absence of rafting. Results On average, 74% of tracked birds engaged in rafting. Of the 381 foraging trips analysed, rafting was recorded on 237 (62%). Birds were more likely to raft on outbound (224 trips, 59%), than inbound journeys (38 trips, 10%). Presence/absence of rafting did not correlate significantly with foraging trip distance or duration nor with duration of nest attendance. The majority of rafting was concentrated in a 2-km radius around the colony within a recently designated seaward SPA extension. Birds showed low individual repeatability in rafting, although there was lower variation within, than among, individuals. Conclusion Our results show that rafting is important for breeding gannets on Grassholm, and a recently designated at-sea SPA encapsulates the core distribution of rafting. Rafting did not appear to be correlated with foraging behaviour. Given the dearth of literature on rafting and the wealth of GPS tracking data for seabirds, we suggest that similar research be conducted elsewhere to further elucidate the ecological and applied significance of this behaviour.